METHANE EMISSION FROM PADDY FIELDS AS INFLUENCED BY DIFFERENT WATER REGIMES IN CENTRAL JAVA - Prihasto Setyanto; Rosenani Abu Bakar (Indonesian Agency for Agricultural Research and Development, 2005)
The concentration of methane (CH4) in the atmosphere is increasing at 1% per annum and rice fields are one of the sources that contribute to about 10-15% of the atmospheric CH4. One of the options to reduce greenhouse gas emission from rice fields is probably through water management. A field study was conducted to investigate the effects of water management practices on CH4 emission from rice field plots on a silty sand Aeric Tropaquept soil at Research Station for Agricultural Environment Preservation, Jakenan, Central Java, Indonesia, during the dry season of March to June 2002. Four water regimes tested were: (1) 5 cm continuous flooding (CF), (2) 0-1 cm continuous flooding (ST), (3) intermittent irrigation (IR) where plots received continuously 5 cm of flooding with two times of draining at 15-20 and 25-30 days after transplanting (DAT), and (4) pulse irrigation (PI) where plots were watered until 5 cm level and left to dry by itself until the water table reached 30 cm beneath soil surface then watered again. The total CH4 emissions of the four water treatments were 254, 185, 136 and 96 kg CH4 ha-1 for CF, ST, IR and PI, respectively. Methane emission increased during the early growing season, which coincided with the low redox potential of -100 to -150 mV in all treatments. Dry matter weight of straw and filled grain among the water treatments did not show significant differences. Likewise, total grain yield at 14% moisture content was not significantly different among treatments. However, this result should be carefully interpreted because the rice plants in all water treatments were infested by stem borer, which reduced the total grain yield of IR64 between 11% and 16%. This study suggests that intermittent and pulse irrigation practices will be important not only for water use efficiency, but also for CH4 emission reduction.